Aerobic Exercise Has Positive Effects on Menstrual Cycle - Linda Desrianda Tamher; Mustika Fitri; Pipit Pitriani (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The purpose of this study was to determine the effect of aerobic exercise on obese women. The research design used was a pretest-posttest two treatment design. The subjects involved in this study were 22 women divided into 2 groups, including the aerobic exercise group and the zumba group. This study was conducted 3 times a week for 12 weeks with 65-85% intensity of the maximum pulse rate. Menstrual cycle data were obtained using the interview technique and menstrual questionnaire. The results of this study indicated that aerobic exercise and zumba did not affect the menstrual cycle. Although the study data showed no increase or decrease in menstrual cycles after endurance training, overall subjects experienced positive psychological improvements and decreased menstrual pain.This study concludes that aerobic exercise is good to do because it does not affect the menstrual cycle.